Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/clc.23713
|View full text |Cite
|
Sign up to set email alerts
|

Isolated diastolic hypertension and target organ damage: Findings from the STANISLAS cohort

Abstract: Background: Isolated diastolic hypertension (IDH) is defined as diastolic blood pressure (DBP) ≥80 mmHg and systolic blood pressure (SBP) <130 mmHg according to 2017 ACC/AHA guidelines. The effective cardiovascular risk linked to IDH is debated. Hypothesis: IDH might contribute marginally to hypertension-related target organ damage (TOD) development. Methods: In this cross-sectional analysis 1605 subjects from the STANISLAS cohort, a large familiar longitudinal study from Eastern France, were included. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
1
6
0
1
Order By: Relevance
“…3H ) and IDH ( Fig. 4H ), which agrees with experimental observations ( Manios et al, 2015 ; Monzo et al, 2021 ). These results suggest the hypothesis that Notch mechanosensitivity is involved not only in the establishment of arterial homeostasis ( Loerakker et al, 2018 ), but also in its maintenance.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…3H ) and IDH ( Fig. 4H ), which agrees with experimental observations ( Manios et al, 2015 ; Monzo et al, 2021 ). These results suggest the hypothesis that Notch mechanosensitivity is involved not only in the establishment of arterial homeostasis ( Loerakker et al, 2018 ), but also in its maintenance.…”
Section: Discussionsupporting
confidence: 91%
“…The stretch distributions were then used as input for the simulation of Notch signaling and, consequently, the prediction of the VSMC phenotypes in the arterial wall. Previous experimental studies have demonstrated that all three types of hypertension result in a thickening of arteries ( Al-Nimer et al, 2010 ; Chen et al, 2011 ; Manios et al, 2015 ; Monzo et al, 2021 ). A synthetic phenotype of VSMCs, inducing arterial G&R, is therefore expected in all these situations.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…7 Another cross-sectional analysis of 1605 French adults in the longitudinal STANISLAS cohort study found that IDH by the ACC/AHA definition was not significantly associated with markers of target organ damage including natriuretic peptides, microalbuminuria, diastolic dysfunction, left ventricular mass, carotid intimal thickness, ankle-brachial indices, and pulse-wave velocity. 30 While existing evidence does not support an association between IDH and subclinical atherosclerosis or target organ damage, it is worth noting that IDH, by both the old and the new definitions, is a strong risk factor for the future development of systolic hypertension. A landmark analysis of the Framingham Heart Study with 5209 participants found that those with IDH by JNC/ESC/ NICE definition were 23 times more likely to develop combined SDH, compared with participants who were normotensive.…”
Section: The 2017 Acc/aha Definition Of Idh and Target Organ Damage/ ...mentioning
confidence: 99%
“…13 that blood flow volume would be reduced by 18.2%. Long-term sustained isolated diastolic hypertension causes insufficient blood supply to the body, which is clinically manifested as heat discomfort, dizziness, listlessness of spirit, and weakness of limbs, among other symptoms (Chrysant 2020;Monzo et al, 2021).…”
Section: Sympathetic Nervous System Peripheral Resistance and Blood S...mentioning
confidence: 99%